Fostering Student Entrepreneurship – A Thematic Analysis Focusing on Major Challenges Faced by Educators - Thangarasa Tiburtrious Andrew Rohanaraj; Pubuduni Jeewandarage; R.P. Chitra Ranjani (Journal of Economics Education and Entrepreneurship, 2026)
Fostering student entrepreneurship in higher educational institutions (HEIs) inculcates the spirit of entrepreneurship in the minds of young individuals and  encourages them to become successful entrepreneurs in future.  Though the concept supports entrepreneurship development, it creates significant challenges to the educators and educational institutions, as conventional wisdom expects the HEIs to focus primarily on academic advancement and scholarship.  This study attempts to understand the major challenges faced by educators, while promoting student entrepreneurship in HEIs. This study used face-to-face interviews to collect information from 23 samples identified through purposive sampling.  The respondents either work-in or lead entrepreneurship development initiatives in their respective HEIs. The ‘Thematic analysis’ identified four major themes, namely, dilemma related to the role of students, importance of a market driven approach, entrepreneurial human capital development and availability of funding options, as major challenges faced by HEIs. The findings add value and variety to existing literature, while providing useful insights to HEIs working towards fostering student entrepreneurship.  The findings could also support decision makers in developing frameworks that encourage investment on appropriate student support mechanisms within HEIs along with possible legal protection to student entrepreneurs. The findings could also act as a point of reference, by future researchers.